The effects of sediment transport on temporal variation in radiocesium concentrations in very shallow water off the southern coast of Fukushima, Japan. (April 2018) - Matsumoto, Akira; Myouse, Hiroshi; Arakawa, Hisayuki; Higuchi, Ken; Hirakawa, Naoto; Morioka, Yoshiaki; Mizuno, Takuji
Abstract: We studied the very shallow coastal water off Iwaki City, Fukushima Prefecture, and investigated: (1) temporal variation in 137 Cs concentrations; (2) particle-size distribution of sediments; and (3) the effect on variation by waves, component-fractionated concentration of radiocesium and mineral composition at three sampling stations (Yotsukura, Ena rocky reef and Ena sandy station). There was a decline in 137 Cs concentrations in sediment samples at all sampling stations between 425 and 1173 days after the accident. All stations had fluctuations in 137 Cs concentrations between 425 and 800 days. At Ena sandy station and Ena rocky reef stations the declines in 137 Cs concentrations slowed from about 800 days after the accident. Fluctuations in particle median diameters were seen, as well as in 137 Cs concentrations. At Yotsukura, where the fluctuation in median diameter was small, a constant decrease in 137 Cs concentrations was observed. We considered that bioturbation may contribute the constant decrease. At Ena sandy station, where the fluctuation of the median diameter was large, the fluctuation in 137 Cs concentrations was also large. The movement of sediments was evaluated by the Shields parameter, and results indicated that at any station where the sediment was moved more frequently, the fluctuation in 137 Cs concentrations was also large. The highly contaminated small particles moved from our stations due to wave action between 425 and 800 days after the accident. The remaining relatively large particles might contribute to the slowing down in reduction of 137 Cs concentrations from 800 days after the accident. However, the 137 Cs concentrations in sediments in very shallow water off the southern coast of Fukushima may continue to decline over time. Highlights: We measured 137 Cs concentrations in sediments in the very shallow coastal water off Fukushima Prefecture. All three locations had fluctuations in 137 Cs concentrations. We considered that sediment transport causes the fluctuation in 137 Cs concentrations. We also considered that bioturbation may contribute the constant decrease in concentration. The degree of these processes varied depending on the location.